Regional dynamics of economic performance in the EU: To what extent do spatial spillovers matter? - Selin Ozyurt; Stéphane Dées (REGION, 2018)
This paper investigates the main determinants of economic perfor-mance in the EU from a regional perspective, covering 253 regions overthe period 2001-2008. In addition to the traditional determinants of eco-nomic performance, measured by GDP per capita, the analysis accountsfor spatial effects related to externalities from neighbouring regions. Thespatial Durbin random-effect panel specication captures spatial feedback-effects from the neighbours through spatially lagged dependent and inde-pendent variables. Social-economic environment and traditional determi-nants of GDP per capita (distance from innovation frontier, physical andhuman capital and innovation) are found to be signicant. Overall, ourndings conrm the signicance of spatial spillovers, as business invest-ment and human capital of neighbouring regions have a positive impactboth direct and indirect on economic performance of a given region.
Keywords: O17; O31; O18; R12; 330; Spatial Durbin Models; spatial spillovers; economic performance